Sustainable innovation types: A bibliometric review - Degler, Thomas; Agarwal, Nivedita; Nylund, Petra A.; Brem, Alexander (International Journal of Innovation Management, 2021)
The synonymic use of sustainable innovation types obstructs the impact of increasingly disperse research on sustainable innovation, environmental innovation, eco-innovation, and green innovation. To identify the meaning and contributions of each innovation type over time, we apply co-word analysis as a bibliometric technique to 1,985 papers, analysing the evolution of motor, emergent and basic themes for each type. For environmental innovation, the focus has shifted from environmental regulations and policies to patents and inventions with an environmental impact, while in sustainable innovations the societal impact of technology adoption has become a driver. Green innovation increasingly concerns environmental technology and its management, whereas eco-innovation studies aspects related to efficiency and decision making. Clear distinctions among sustainable innovation types will increase the impact of this expanding body of research and make it more available to managers and policymakers.
CRIS-Team Scopus Importer:2021-12-24
Keywords: bibliometric review; eco-innovation; environmental innovation; green innovation; Sustainable innovation